Criminal procedural conflicts - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2024)
Criminal procedural conflicts are a type of sectoral legal conflicts. They arise between participants in criminal proceedings who have opposing interests and goals. Their occurrence is associated with the presence of a criminal legal conflict (crime). It is necessary to differentiate between the concepts and phenomena «legal conflict» and «juristic conflict». A legal conflict is a potential conflict. The model for its prevention and resolution is laid down in legislation. A juristic conflict is a legal conflict realised in the actions of subjects. The legislation regulates the resolution of criminal procedural conflicts between professional lawyers (judge, prosecutor, investigator, defense lawyer) in sufficient detail. In resolving any criminal procedural conflicts, the discretion of the law enforcement officer is essential.
Keywords: conflict; criminal procedure; criminal case; subject; court; prosecutor; investigator; defense lawyer